INTELLIGENT STRUCTURING OF RUSSIAN TEACHING TEXTS IN A DIGITAL EDUCATIONAL ENVIRONMENT FOR A TURKIC-SPEAKING AUDIENCE - Silantiev V.V.; Miftakhutdinova D.N.; Terekhin A.A.; Chukmarov I.A. (Uzbekistan Open Conference, 2026)
The theses address the problem of how students in a Turkic-speaking audienceunderstand Russian teaching texts. The paper emphasizes that comprehension difficulties are related notonly to vocabulary and grammar but also to the way ideas are developed, the discourse-syntacticorganisation of the text, the linear-thematic organisation of the paragraph, and the distribution of core andexplanatory information. It is argued that digital and intelligent structuring of teaching texts can become aneffective tool for pedagogical adaptation in a multilingual educational environment only if the restructuringis carried out with due regard for the discourse-syntactic norms of Turkic languages and their typical patternsof paragraph development.
Keywords: Russian teaching text; Turkic-speaking audience; digital educational environment; intelligent structuring; discourse-syntactic adaptation; linear-thematic paragraph organization